2008
DOI: 10.1128/aem.00054-08
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Genome Sequence ofLactobacillus gasseriATCC 33323 Reveals the Molecular Basis of an Autochthonous Intestinal Organism

Abstract: This study presents the complete genome sequence of Lactobacillus gasseri ATCC 33323, a neotype strain of human origin and a native species found commonly in the gastrointestinal tracts of neonates and adults. The plasmid-free genome was 1,894,360 bp in size and predicted to encode 1,810 genes. The GC content was 35.3%, similar to the GC content of its closest relatives, L. johnsonii NCC 533 (34%) and L. acidophilus NCFM (34%). Two identical copies of the prophage LgaI (40,086 bp), of the Sfi11-like Siphovirid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
147
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 154 publications
(152 citation statements)
references
References 103 publications
3
147
0
2
Order By: Relevance
“…Supplementary material related to the published genome sequence of DSM 20243 (Azcarate-Peril et al, 2008) indicated the presence of two gene loci, LGAS_1281 and LGAS_1282, with assigned functions in fructan synthesis. However, analysis of the genome sequence (GenBank accession no.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Supplementary material related to the published genome sequence of DSM 20243 (Azcarate-Peril et al, 2008) indicated the presence of two gene loci, LGAS_1281 and LGAS_1282, with assigned functions in fructan synthesis. However, analysis of the genome sequence (GenBank accession no.…”
Section: Resultsmentioning
confidence: 99%
“…3b). In a recent report (Azcarate-Peril et al, 2008), none of the nine L. gasseri strains tested, including the type strain (DSM 20243), was found to ferment raffinose. We also could not detect any growth or product formation by the three L. gasseri strains used in our studies, not even after 5 days of incubation with 500 mM raffinose (Fig.…”
Section: Kinetic Parametersmentioning
confidence: 93%
See 1 more Smart Citation
“…The adhesion of L. rhamnosus GG cells to intestinal mucus was inhibited by anti-MBF serum using the procedure described previously (21,41). Briefly, 3 H-labeled wild-type (WT) L. rhamnosus GG cells were first preincubated with anti-SpaC pilin serum (diluted 1:100) and then treated either with or without anti-MBF serum (diluted 1:100). Antibody-untreated WT L. rhamnosus GG served as a positive adhesion control.…”
Section: Bacterialmentioning
confidence: 99%
“…Moreover, homology-driven genome mining in several Lactobacillus spp. (3,7,8,11,33) has identified the presence of various-sized putative mucus adhesins consisting of one or more copies of an approximately 100-to 200-amino-acid (aa) mucus-binding (MUB) domain repeat, which, given its prevalence in lactic acid bacteria (LAB), can be considered a unique functional feature for promoting host-microbe interplay in the GI tract (7).…”
mentioning
confidence: 99%